SURGICAL MANAGEMENT OF TEMPOROMANDIBULAR JOINT ANKYLOSIS: INITIAL EXPERIENCES - Celal Çandırlı; Ezher Dayısoylu; Fatih Taskesen (Cumhuriyet University, 2014)
Objective: The aim of this study is to introduce our initial clinical experience in the operative management of temporomandibular joint (TMJ) ankylosis. Study design: This retrospective study assessed 8 patients with TMJ ankylosis who underwent different surgical procedures. Gap arthroplasty with temporalis muscle and fascia flap repositioning was performed in 6 patients, transport distraction osteogenesis was performed to form a neocondyle in one patient and TMJ prosthesis was replaced in one patient. Patients were followed weekly at first month and at months 3rd, 6th, 12th, and 24th postoperatively. Patients were evaluated in terms of maximum interincisal opening and occlusal stability in each appointment. Results: Mean preoperative Maximum interincisal opening (MIO) of 11 mm (2-14 mm) was improved to 31mm (26-35 mm). All patients had satisfactory mandibular motions 2 years after the operation and reankylosis was not observed in patients. Conclusion: Radiological and clinical evaluation should be carefully performed to avoid possible intraoperative and postoperative complications in the management of TMJ ankylosis. Consistent with the literature, it was observed that temporalis musculofascial flap repositioning is successful to avoid reankylosis